f(x+4)=6x-7

Simple and best practice solution for f(x+4)=6x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(x+4)=6x-7 equation:


Simplifying
f(x + 4) = 6x + -7

Reorder the terms:
f(4 + x) = 6x + -7
(4 * f + x * f) = 6x + -7
(4f + fx) = 6x + -7

Reorder the terms:
4f + fx = -7 + 6x

Solving
4f + fx = -7 + 6x

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Reorder the terms:
7 + 4f + fx + -6x = -7 + 6x + 7 + -6x

Reorder the terms:
7 + 4f + fx + -6x = -7 + 7 + 6x + -6x

Combine like terms: -7 + 7 = 0
7 + 4f + fx + -6x = 0 + 6x + -6x
7 + 4f + fx + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
7 + 4f + fx + -6x = 0

The solution to this equation could not be determined.

See similar equations:

| -y+148=274 | | -w+266=151 | | L=100w | | 25x-30x=5-10 | | x=100y | | 162=229-w | | h(t)=16t^2+65t+3.5 | | -0.65x^3+0.57x^2+56.68x+3104= | | x-3/4x-3=4 | | (y^2+y)-7(4y^2-5y)+2= | | x^2+bx+15=0 | | (-2x+8)=0 | | (3x+6)=6 | | (-2-x)=9 | | (x)=-0.65x^3+0.57x^2+56.68x+3104 | | (4x-2)=-6 | | 3.5(6x-2)=3.5 | | 5(-3.1x+6.9)=-3.5 | | 5z=2.3+4.2 | | x*20/3=5/6 | | -0.3(3+8x)=0.9 | | -3(2x+1.2)=-1 | | 12/19=-4z | | 0=-0.5x^2+7x-20 | | 8x+82x=80 | | 9=3y+37+4y | | 5/2t=-7/3 | | x=-0.5x^2+7x-20 | | -12x^2+42x-20=0 | | -(2x-10)-1=2 | | 3a^2+27b^2+5c^2-18ab-30c=-237 | | 12x^2-42x-20=0 |

Equations solver categories